If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4x = 1thrid(6x + 9) Reorder the terms: 6 + 4x = 1dhirt(9 + 6x) 6 + 4x = (9 * 1dhirt + 6x * 1dhirt) 6 + 4x = (9dhirt + 6dhirtx) Solving 6 + 4x = 9dhirt + 6dhirtx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6dhirtx' to each side of the equation. 6 + -6dhirtx + 4x = 9dhirt + 6dhirtx + -6dhirtx Combine like terms: 6dhirtx + -6dhirtx = 0 6 + -6dhirtx + 4x = 9dhirt + 0 6 + -6dhirtx + 4x = 9dhirt Add '-6' to each side of the equation. 6 + -6dhirtx + -6 + 4x = -6 + 9dhirt Reorder the terms: 6 + -6 + -6dhirtx + 4x = -6 + 9dhirt Combine like terms: 6 + -6 = 0 0 + -6dhirtx + 4x = -6 + 9dhirt -6dhirtx + 4x = -6 + 9dhirt Reorder the terms: 6 + -9dhirt + -6dhirtx + 4x = -6 + 9dhirt + 6 + -9dhirt Reorder the terms: 6 + -9dhirt + -6dhirtx + 4x = -6 + 6 + 9dhirt + -9dhirt Combine like terms: -6 + 6 = 0 6 + -9dhirt + -6dhirtx + 4x = 0 + 9dhirt + -9dhirt 6 + -9dhirt + -6dhirtx + 4x = 9dhirt + -9dhirt Combine like terms: 9dhirt + -9dhirt = 0 6 + -9dhirt + -6dhirtx + 4x = 0 The solution to this equation could not be determined.
| a^6-b^6=0 | | 21+6p=9p | | 5-4x=3+2x | | 33=5m-12 | | 4(-5x+4)-6x=120 | | 4x+3=-1 | | y=2x^2+24x+72 | | 4x^2+60=0 | | h/3+5=-8 | | -0.5m+-3=9 | | 7k+4+4k-9-5k= | | y=2x^2-24x+72 | | .5m-3=9 | | -90+w=-10 | | v+7v-2v^2=30 | | 3-4x-4x^2= | | 3+6u=63 | | -3-4x-4x^2= | | v+7v=-12 | | 37+8x=-4(7-x) | | 14y^2-9y+3= | | 4x+3-6x=12 | | x-2(-2)=6 | | 14=2-x | | 7x+21=-9(x+3) | | 2a+5=5 | | 3x^2+20x-7= | | x=-2x^2+8x+10 | | 6+3x=-9 | | 7-2=4s-5 | | 23-X=2X+8 | | 6n+3=7+2n |